2013
DOI: 10.1186/2050-6511-14-12
|View full text |Cite
|
Sign up to set email alerts
|

Empiric guideline-recommended weight-based vancomycin dosing and nephrotoxicity rates in patients with methicillin-resistant Staphylococcus aureus bacteremia: a retrospective cohort study

Abstract: BackgroundPrevious studies have established a correlation between vancomycin troughs and nephrotoxicity. However, data are currently lacking regarding the effect of guideline-recommended weight-based dosing on nephrotoxicity in methicillin-resistant Staphylococcus aureus bacteremia (MRSAB).MethodsAdults who were at least 18 years of age with methicillin-resistant Staphylococcus aureus bacteremia and received of empiric vancomycin therapy for at least 48 hours (01/07/2002 and 30/06/2008) were included in this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…A multicenter prospective clinical trial, including 288 adult patients (70), and a recent meta-analysis (71) have reaffirmed the high probability of nephrotoxicity with vancomycin trough levels of Ͼ15 mg/liter. This threshold is not uniform in all studies, and other authors have found that recommended dosages of vancomycin with target troughs of 15 to 20 mg/liter are not an independent risk factor for nephrotoxicity (72). Davies et al (73) found that vancomycin was related to a rise in creatinine levels only with trough levels of Ͼ20 mg/liter.…”
Section: Vancomycin Toxicitymentioning
confidence: 94%
“…A multicenter prospective clinical trial, including 288 adult patients (70), and a recent meta-analysis (71) have reaffirmed the high probability of nephrotoxicity with vancomycin trough levels of Ͼ15 mg/liter. This threshold is not uniform in all studies, and other authors have found that recommended dosages of vancomycin with target troughs of 15 to 20 mg/liter are not an independent risk factor for nephrotoxicity (72). Davies et al (73) found that vancomycin was related to a rise in creatinine levels only with trough levels of Ͼ20 mg/liter.…”
Section: Vancomycin Toxicitymentioning
confidence: 94%
“…Our patients had several risk factors that are typically associated with vancomycin nephrotoxicity: high trough concentrations, 9,10 obesity, 11 concomitant administration of piperacillin-tazobactam, and in a few patients, aminoglycosides. 12, 13 A recent study has suggested that piperacillin-tazobactam increases vancomycin-induced nephrotoxicity, but we failed to reproduce this finding experimentally in mice.…”
Section: Introductionmentioning
confidence: 99%
“…The association between VT or vancomycin total daily dose and AKI has been described in several studies [4,5,[8][9][10][11][12][13][14] . However, some studies demonstrated that higher VT level of 15-20 is not more associated with AKI than lower levels [7,15,16] .…”
Section: Discussionmentioning
confidence: 99%